Investasi ditinjau dari Perspektif Ekonomi dan Ekonomi Islam - Putri Ramadhani, Azahra; Afifah Septyasari, Indah; Nur Hasannah, Fajriah; Kustiawati, Dedek (Jurnal Indonesia Sosial Sains, 2022)
Investment is spending or spending to buy capital goods or equipment to increase the ability to produce goods or services. Many investments are made by the community in order to increase the value of the assets they have. Investment has many very useful benefits in the future. Investment really needs to be done so that economic development runs smoothly so that people feel prosperous. Even in Islam, investment is highly recommended. The method used in this research is the literature study method. Based on the research results that have been reviewed, there are two foundations for investing, namely the Qur'an and Hadith. Before making an investment, there are things that need to be considered, namely the terms or conditions that are permissible and prohibited in order to achieve benefits for oneself in this world and the hereafter. It can be concluded that before investing, investors must understand the concept of investment, investment principles, investment objectives, types of investment, the benefits of investing, even what risks are likely to occur when making an investment.